Evaluation of phytochemical analysis and antibacterial activity of Bauhinia purpurea L. and Hiptage benghalensis L. Kurz - Murugan M, Mohan V.R. (Journal of Applied Pharmaceutical Science)
Phytochemicals from the leaves and stem bark of Bauhinia purpurea and Hiptage benghalensis were extracted using different solvents of various polarities such as petroleum ether, chloroform, acetone, methanol and water. The antibacterial activity was carried out against Staphylococcus aureus, Klebsiella pneumoniae, Bacillus subtilis, Escherichia coli, Pseudomonas aeruginosa and Salmonella typhi by disc diffusion method. Among the solvent extracts, methanol extract was most effective against the tested microorganisms. Phytochemical analysis revealed the presence of alkaloids, coumarin, flavonoids, phenols, tannins and terpenoids.
Keywords: Phytochemicals, antibacterial activity, disc diffusion, Hiptage benghalensis, Bauhinia purpurea.